2022
DOI: 10.3389/fcvm.2022.996225
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods for predicting major types of rheumatic heart diseases in children of Southern Punjab, Pakistan

Abstract: ObjectiveRheumatic heart disease (RHD) is a major health problem in the world, particularly in developing countries. This study aimed to predict mitral regurgitation (MR) and mitral stenosis (MS) RHD among children with RHD.MethodologyData was collected from the Pediatric Cardiology Department at Chaudhry Pervaiz Elahi Institute of Cardiology Multan, Pakistan from March to October 2019. A sample of 561 children aged 4–14 years, who were diagnosed with RHD of either MR or MS, were recruited from the hospital’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…26 This study discovered that the mean left ventricular posterior wall end diastole and end systole (LVPWd) was found to be 10.01±1.18mm. This finding is higher than a study conducted in Multan, Pakistan, where the mean LVPWd was reported as 7.13 ± 1.95mm 27 and another study by Meel et al from South Africa also reported a mean LVPWd of 8.5 ± 1.5mm. 28 Differences in LVPWd among studies may be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 67%
“…26 This study discovered that the mean left ventricular posterior wall end diastole and end systole (LVPWd) was found to be 10.01±1.18mm. This finding is higher than a study conducted in Multan, Pakistan, where the mean LVPWd was reported as 7.13 ± 1.95mm 27 and another study by Meel et al from South Africa also reported a mean LVPWd of 8.5 ± 1.5mm. 28 Differences in LVPWd among studies may be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 67%